2017
DOI: 10.4028/www.scientific.net/kem.730.42
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Pineapple Leaf Fiber Reinforced Epoxy Based Composites

Abstract: The present study investigates the dielectric constant, loss factor and dissipation factor of pineapple leaf fiber reinforced epoxy composites as in function of fiber loading, fiber surface modification and frequency. The dielectric properties of the composites were measured using HP 16451 as the dielectric test fixture and was carried out on pineapple leaf fiber reinforced epoxy composites with varying fiber loading (5wt%, 10wt%, 15wt%, and 20wt%) and fiber subjected to sodium hydroxide treatment. It was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is noticed that the dissipation factor and loss factor increase with fibre loading but decreases with increased frequency. Journal reported that dissipation and loss factor of PALF/Epoxy composite decreases at all frequency but increase with increased in fibre content [16]. Figure 3 display the effect of fibre content of PALF and jute on dissipation factor of hybrid composite.…”
Section: Effect Of Fibre Contentmentioning
confidence: 95%
See 2 more Smart Citations
“…It is noticed that the dissipation factor and loss factor increase with fibre loading but decreases with increased frequency. Journal reported that dissipation and loss factor of PALF/Epoxy composite decreases at all frequency but increase with increased in fibre content [16]. Figure 3 display the effect of fibre content of PALF and jute on dissipation factor of hybrid composite.…”
Section: Effect Of Fibre Contentmentioning
confidence: 95%
“…Besides that, the dielectric constant of kenaf fibre increases as the temperature increase with constant frequency of 100Hz. Moreover, the dielectric constant of kenaf fibre with highest fibre loading is lower compared to jute, palf [16] and bamboo fibre [24]. Dissipation factor of jute/bamboo hybrid composite decreases as the frequency increase and fibre content decrease [24].…”
Section: Effect Of Fibre Contentmentioning
confidence: 95%
See 1 more Smart Citation
“…Among these, pineapple leaves, often discarded as waste after harvesting the fruit, boast promising chemical composition and mechanical properties that can be harnessed to produce valuable natural fibers [7]. Transforming pineapple leaves into dielectric material for electrical appliances is a sustainable approach that adds value to pineapple waste [7,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing cellulose derived from pineapple waste as a filler in composite materials opens up possibilities for applications in electronics devices such as capacitors, insulators, printed circuit boards (PCBs), sensors, and diverse types of antennas [17][18][19][20]. This approach not only allows for the full utilization of natural resources but also contributes to the development of novel dielectric composite materials from pineapple waste [11]. A composite material is defined by the incorporation of diverse elements to achieve specific characteristics and functionalities.…”
Section: Introductionmentioning
confidence: 99%